A new leaf-tying Episimus Walsingham (Lepidoptera: Tortricidae) feeding on the vulnerable tree Haplorhus peruviana (Anacardiaceae) in the Atacama Desert of northern Chile. (4th May 2018) - Brito, Rosângela; Vargas, Héctor A.
ABSTRACT: Episimus Walsingham, 1892 (Lepidoptera: Tortricidae: Olethreutinae: Olethreutini) is reported for the first time from Chile. Male and female adults of Episimus buarquei Brito & Vargas sp. n. are described and illustrated based on specimens reared from larvae collected on the vulnerable native tree Haplorhus peruviana Engler (Anacardiaceae) in the Chaca Valley, Atacama Desert of northern Chile. DNA barcode sequences of the cytochrome c oxidase subunit I mitochondrial gene are provided and used to preliminarily assess the relationships of E. buarquei with congeneric species. http://zoobank.org/urn:lsid:zoobank.org:pub:CDD4BF83-F8AB-4644-8047-77793AB43CA6